Patient attitudes towards outpatient cervical ripening prior to induction of labour at an Australian tertiary hospital. (2nd October 2016) - Sutton, Claire; Harding, Julia; Griffin, Christopher
Abstract: A prospective patient questionnaire was conducted to assess attitudes and opinions towards outpatient cervical ripening in women attending an Australian tertiary hospital's labour and birth suite for a booked induction of labour. Questionnaires were distributed over a three-month period and information collected included demographic data, pregnancy and obstetric history, attitudes towards cervical ripening and willingness to undergo cervical ripening in the outpatient setting. Responses to 57 completed questionnaires were analysed. Forty-one patients (72%) underwent cervical ripening with Foley Catheter Balloon (FCB) only, eight (14%) with FCB and vaginal prostaglandins (VP), two (3.5%) with VP only and six patients (10.5%) did not require cervical ripening. One-third (33%) of patients stated, both before the commencement of cervical ripening and after delivery, that they would feel happy to undergo outpatient cervical ripening. Patient acceptance of outpatient cervical ripening has potential economic and psychosocial benefits for the healthcare system and patient respectively.